PENGEMBANGAN MEDIA PEMBELAJARAN PAI DENGAN MENGGUNAKAN VIDEO EXPLANASI, POP UP DAN KAHOOT - Himatul Ulya; Noer Hidayatul Laily; Mukhamad Luqman Hakim (Institut Agama Islam Negeri Kediri, 2020)
Abstract: In education, an educator is required to be able to condition a conducive classroom atmosphere in learning activities. Learning itself does not only depend on learning strategies, but the use of appropriate media is an important factor in motivating student learning. The phenomenon that occurs in the world of education today is that educators lack the use of the media in teaching activities, especially in learning Islamic Education. Whereas in learning PAI, there are often difficulties in understanding the materialbecause it is often associated with the proposition and application of daily activities, which incidentally will not be maximized if only using the lecture method. So in this article, researchers show the results of the implementation of instructional media in the form of video explanations, Pop ups and Kahoot in SMA 6 KOTA KEDIRI. The development of interactive learning media uses research and development methods of Research and Development, in which researchers propose a new combination of products that innovateto cover these problems through media that are felt to have more effective learning effects Specifically Islamic education. From the regression analysis, the test results through SPSS show that Sig less than 0.05 which means that Ho is rejected. That means there is an influence of multimedia learning in improving the effectiveness of PAI learning. The relatively dynamic relationship shows that multimedia learning is interesting in order to increase student learning effectiveness. Abstrak: Dalam pendidikan, seorang pendidik diharuskan mampu mengkondisikan suasana kelas yang kondusif dalam kegiatan belajar. Pembelajaran sendiri tidak hanya tergantung pada strategi pembelajaran, namun penggunaan media yang tepat merupakan faktor penting dalam memotivasi belajar peserta didik. Fenomena yang terjadi pada dunia pendidikan saat ini adalah pendidik kurang memanfaatkan media dalam kegiatan mengajar terutama dalam pembelajaran Pendidikan Agama Islam. Padahal dalam pembelajaran PAI sering terjadi kesulitan dalam memahami materi lantaran sering dikaitkan dengan dalil dan penerapan kegiatan sehari-hari, yang notabenenya hal itu tidak akan maksimal jika hanya menggunakan metode ceramah. Sehingga dalam artikel ini, peneliti menunjukan hasil implementasi dari media pembelajaran berupa video explanasi, Pop up dan Kahoot di SMA NEGERI 6 KOTA KEDIRI. Pengembangan media pembelajaran interaktif tersebut menggunakan metode penelitian dan pengembangan Research and Development, dimana peneliti mengajukan sebuah produk kombinasi baru yang berinovasi mengcover permasalahan tersebut melalui media yang dirasa lebih memberikan dampak efektifitas pembelajaran Khususnya pendidikan Agama Islam. Dari analisis regresi, hasil uji melalui SPSS menunjukkan bahwa Sig kurang dari 0,05 yang artinya bahwa Ho ditolak. Itu artinya ada pengaruh pembelajaran multimedia dalam meningkatkan efektifitas pembelajaran PAI. Hubungan yang relatif dinamis menunjukkan bahwa pembelajaran multimedia menarik dalam rangka meningkatkan efektifitas belajar siswa.